Ambulatory isolated systolic hypertension and target organ damage in a South African population - Mlambo, Bongubuhle Wanelisile (My University, 2020)
Isolated systolic hypertension is a major contributor to renal and cardiovascular disease morbidity and mortality worldwide, however, its prevalence in the adult population of African ancestry in South Africa is unknown. Moreover, the existence and effects of ambulatory types of this condition on vital organ systems have not been fully investigated. The aim of this study was to determine prevalence of, and target organ changes associated with, conventional and ambulatory subtypes of Isolated Systolic Hypertension. A total of 549 participants underwent general clinical and ambulatory blood pressure measurements by whose outcome they were divided into four Isolated Systolic Hypertension subtypes (Conventional, Daytime, Night-time and 24-hour Isolated Systolic Hypertension) and two control groups (Systolic-Diastolic Hypertensives and normotensives). Participants further underwent measurements of Pulse Wave Velocity, Left Ventricular Mass Index and Microalbuminuria to determine the extent of arterial stiffness, left ventricular hypertrophy and renal dysfunction associated with the subtypes of Isolated Systolic Hypertension, respectively. The prevalence of Conventional Isolated Systolic Hypertension, 24-hour Isolated Systolic Hypertension, Night-time Isolated Systolic Hypertension and Daytime Isolated Systolic Hypertension was 7.5%, 7.1%, 7.7% and 7.5% respectively. All subtypes of the condition emerged as strong predictors of Pulse Wave Velocity, Left Ventricular Mass Index and Microalbuminuria. Furthermore, similarly increased Pulse Wave Velocity was observed in the 24-hour Isolated Systolic Hypertension subtype and hypertensives. Greater Left Ventricular Mass Index was observed in the Conventional Isolated Systolic Hypertension subtype compared to hypertensives, whereas microalbuminuria was clinically present in the Night-time Isolated Systolic Hypertension group significantly more than it occurred in the hypertensive control group. Overall, this study revealed that Isolated Systolic Hypertension is prevalent in both clinical and ambulatory sub-types in this populations, and that it is associated with arterial stiffness, increased left ventricular mass and renal dysfunction equal to or exceeding the detrimental effects of hypertension on the arteries, heart and kidneys.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Physiology, University of the Witwatersrand, Johannesburg, 2020